Interrelation between functional constipation and domestic violence - Coronel, Ana Lucia Couto; Silva, Helena Terezinha Hubert (Journal of Coloproctology, 2018)
Introduction Functional disorders of the digestive system are often related to various forms of abuse and the integral approach of the problem requires a multidisciplinary network. The objectives of this research were: to evaluate the prevalence of domestic violence in adults with functional constipation and to identify the services and standards available to care for the victims.Methodology The study was developed in two complementary parts. Part I: A cross-sectional study, which evaluated the prevalence of domestic violence in patients attended in the coloproctology outpatient clinic of the Hospital Materno-infantil Presidente Vargas, from September to December 2016. Part II: A narrative review, with bibliographical and documentary research that sought to identify the services and norms available in Brazil to assist victims of domestic violence.Results 146 women were evaluated, 42 of whom had FC and, of these, 26 had a history of domestic violence (p = 0.007), with an Odds Ratio of 2.71 (CI95% O: 1.29–5.67). A network of services has been identified to assist victims of violence, the Network of Attention to Violence, formed by the health services, social assistance, public security, justice, human rights, and organized civil society. However, a standard system for the operation of this network has not been identified.Conclusion The prevalence of domestic violence in women with functional constipation is high and a careful investigation of this possible interrelationship in clinical practice is suggested. Besides that, it is necessary to promote an integration of the Network of Attention to Violence, in order to offer integral care to the victims and a best utilization of the resources.
Keywords: Domestic violence; Constipation; Digestive system; Health care